Early Numeracy Learning Based on Vignette Activity Sequence (VAS) Using Number Boards for Students with Cerebral Palsy - Arianto, Jessica Aspasyah Henda; Damayanti, Nia Wahyu (Jurnal Likhitaprajna, 2026)
This study aims to explore the early numeracy learning process of a student with cerebral palsy (CP) through the Vignette Activity Sequence (VAS) using a magnetic number board as an adaptive manipulative medium, focusing on the student's engagement, obstacles encountered, and responses at each stage of the activity. A qualitative single case study design was employed, involving one 12 year old female student with spastic quadriplegic CP at a special education elementary school in Surabaya, Indonesia. Data were collected through a task analysis-based observation sheet, field notes, and video documentation during a single structured learning session, then analyzed using the Miles and Huberman model with triangulation across all three data sources. The findings revealed that the student actively engaged in all VAS stages despite significant fine motor difficulties, consistently demonstrating counting-on ability, while counting-back ability did not emerge verbally. The adaptive magnetic number board and contextual narrative effectively supported cognitive, motor, and affective engagement, with movement fluency improving through repeated interaction. The study concludes that VAS combined with adaptive manipulative media has strong potential to support inclusive early numeracy learning for students with CP through meaningful, multisensory, and structured mathematical experiences.